The benefits of argumentation are cross-culturally robust: The case of Japan. (2nd January 2016) - Mercier, H.; Deguchi, M.; Van der Henst, J.-B.; Yama, H.
Abstract: Thanks to the exchange of arguments, groups outperform individuals on some tasks, such as solving logical problems. However, these results stem from experiments conducted among Westerners and they could be due to cultural particularities such as tolerance of contradiction and approval of public debate. Other cultures, collectivistic cultures in particular, are said to frown on argumentation. Moreover, some influential intellectual movements, such as Confucianism, disapprove of argumentation. In two experiments, the hypothesis that Easterners might not share the benefits of argumentation was tested. In Experiment 1, Japanese participants had to solve a standard logical problem individually and then in groups. They performed significantly better in groups. In Experiment 2, Japanese participants had to estimate the weight of various animals. They did so individually, then after learning of another participant's estimates, then after discussing these estimates with the other participant, and then individually again. While the Japanese participants also benefitted from the discussion, these benefits were only visible when participants provided a final individual estimate. This delay is interpreted as reflecting the pressure to preserve social harmony that would have constrained Japanese participants to yield to their partner even when knowing that this did not improve the accuracy of their answer.